PERAN SUGESTI BAGI ORANG KALANG DALAM MELESTARIKAN TRADISI KALANG DI DESA LUMANSARI, KENDAL (The Role of Suggestion on Kalang People in Preserving Kalang Tradition on Lumansari Village, Kendal) - Nur Laili Noviani (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
There are many variants of Islam in Indonesia that is influenced by culture. One of them is Islam Kalang. The Islam Kalang or Kalangese Moslem refers to Moslem people whose their ancestor is Kalang. Even though they are Moslem, they still perform the Kalangese traditions that are not in line with Islamic teaching. These traditions are still being held in their daily life in certain time. One of the factors that influenced their belief on the tradition is a suggestion. This qualitative research aims to describe the suggestion role of the Kalangese Moslem in preserving theKalangese’s traditions. Lumansari village in Kendal is one of the places where Kalangese Moslem resided. Based on the interviews and observation, it is found that suggestion has an important role in influencing Kalang people’s believes to conduct Kalang tradition until now. This suggestion happened because the requirements are fulfilled such as suggestion because of these following reasons thought hindrance, dissociation, majority, authority and willingness to believe. Three of those play significant roles in building Kalang people’s perspectives and  mindset, and even it can affect on their daily social interaction.